A Hydroacoustic Assessment of the Density, Size, and Biomass of Fish in a Freshwater Reservoir After Non-Classical Biomanipulation - Aihuan Guo; Qingping Lian; Pengcheng Sheng; Aiju Zhang; Julin Yuan; Kohji Iida (Fishes)
Monitoring changes in fishery resources, such as the density and growth of fish, following large-scale fish stocking in a reservoir is important. In this study, BioSonics DT-X (201 kHz) was used to assess the seasonal changes in the density, size distribution, and biomass of fish in Duihekou Reservoir, Zhejiang province, China, in 2020. The fish density was significantly lower in spring (3.33 ind./1000 m3) than in summer (75.24 ind./1000 m3), autumn (56.22 ind./1000 m3), and winter (20.37 ind./1000 m3) (p < 0.01). No significant difference in fish density was apparent between summer and autumn. Additionally, the average target strength (TS) values in spring (−41.05 dB) were significantly higher than in summer (−44.66 dB) and autumn (−45.55 dB) (p < 0.01), but significantly higher in winter (−38.12 dB) than in the other seasons (p < 0.01); no significant difference was observed between the summer and autumn values (p > 0.01). The fish biomass in winter (14.3 g/m3) was 13 times that in spring (1.1 g/m3). These results indicate that large-scale fish stocking can effectively adapt to reservoir habitats to achieve growth. The catch composition revealed silver carp (Hypophthalmichthys molitrix) and bighead carp (Aristichthys nobilis) to be dominant species, mostly comprising young individuals. Stock enhancement plays a critical role in reshaping the fishery population structure in a reservoir. These findings enhance our understanding of fishery resource changes in reservoirs after non-classical biomanipulation and demonstrate how hydroacoustic techniques can be successfully used to quantify the density and size distribution of fish for more effective fishery management.